1994
DOI: 10.1007/s002580050024
|View full text |Cite
|
Sign up to set email alerts
|

Fetal rat glandular stomach epithelial cells differentiate into surface mucous cells which express cathepsin E in the absence of mesenchymal cells in primary culture

Abstract: It is well established that the differentiation of glandular stomach epithelial cells is affected by many factors including epithelial-mesenchymal interactions. To clarify the control mechanism of their differentiation, we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…The present study has shown both in vivo and in vitro that the differentiation of Pg-producing cells occurs after the epithelial cell replacement and correlates well with morphogenesis of the adult glands, which are different from the larval glands and are characteristically accompanied by development of the connective tissue [11,12]. In the stomach of higher vertebrates, there is a growing body of evidence that the mesenchyme, which is the origin of the connective tissue, regulates morphogenesis of the glands and expression of Pg [4,42,43]. It is possible that some mesenchymal factor(s) may be involved in the differentiation of Pg-producing cells during anuran metamorphosis just like during organogenesis of the stomach in higher vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has shown both in vivo and in vitro that the differentiation of Pg-producing cells occurs after the epithelial cell replacement and correlates well with morphogenesis of the adult glands, which are different from the larval glands and are characteristically accompanied by development of the connective tissue [11,12]. In the stomach of higher vertebrates, there is a growing body of evidence that the mesenchyme, which is the origin of the connective tissue, regulates morphogenesis of the glands and expression of Pg [4,42,43]. It is possible that some mesenchymal factor(s) may be involved in the differentiation of Pg-producing cells during anuran metamorphosis just like during organogenesis of the stomach in higher vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Since epithelial cell differentiation and migration of gastric glands is thought to be closely linked, the reason why only the former is disturbed is not clear. Recently, epithelial-mesenchymal interactions have attracted attention due to an alteration in miscellaneous conditions and their role in organogenesis [8,9,12]. The question of whether the organization of an IM lesion might be influenced by interstitial cells clearly warrants further study.…”
Section: Discussionmentioning
confidence: 98%
“…In fetal rat gut the mesenchyme enables morphogenesis and cytodifferentiation of crypt and embryonic progenitor cells (Kedinger et al 1986). Fukamachi et al (1994) reported that glandular epithelial cells from fetal rat stomachs differentiate into surface mucous cells in the absence of mesenchymal cells in primary culture, but apparently no parietal and zymogenic cells appear. Even the organization of the stroma has been shown to be important to maintain normal epithelial cell differentiation processes in the glandular stomach of adult mice (Fukamachi 1986).…”
Section: Discussionmentioning
confidence: 99%